2013
DOI: 10.1002/asia.201300143
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic Mixed‐Valence Copper(I,II) Cyanides that were Tuned by Using the Chelate Effect: Discovery of Famous Cairo Pentagonal Tiling and Unprecedented (3,4)‐Connected {83}2{86} Topological 3D Net

Abstract: By using environmentally friendly [Ni(CN)4](2-) as a cyanide source, three new heterometallic cyano-bridged mixed-valence Cu(I)/Cu(II) coordination polymers with three different electronic configurations (d(8)-d(10)), that is, [Cu2Ni(CN)5(H2O)3] (1), [Cu2Ni(CN)5(pn)H2O] (2), and [Cu3Ni(CN)6(pn)2] (3, pn = 1,2-propane diamine) have been synthesized by gradually increasing the amount of pn. Compound 1, which was hydrothermally synthesized in the absence of pn ligand, exhibits the famous 2D Cairo pentagonal tilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…However, the metrics of the (nonplanar) pentagons here is of course different from that in the classical Cairo tiling and the network is visually closer to the topologically equivalent basketweave tiling since, while the four edges ending in a Cd II vertex have close to the same length, that containing the uranyl cation linker is nearly twice as large. Few examples of the Cairo tiling topological type have been reported in metal–organic assemblies, , and, to the best of our knowledge, none in a uranyl compound. As in complexes 1 – 4 and 8 , the cyclohexyl rings protrude on both sides of the layers, and the packing does not contain free spaces (KPI 0.72, or 0.69 with solvent excluded).…”
Section: Resultsmentioning
confidence: 99%
“…However, the metrics of the (nonplanar) pentagons here is of course different from that in the classical Cairo tiling and the network is visually closer to the topologically equivalent basketweave tiling since, while the four edges ending in a Cd II vertex have close to the same length, that containing the uranyl cation linker is nearly twice as large. Few examples of the Cairo tiling topological type have been reported in metal–organic assemblies, , and, to the best of our knowledge, none in a uranyl compound. As in complexes 1 – 4 and 8 , the cyclohexyl rings protrude on both sides of the layers, and the packing does not contain free spaces (KPI 0.72, or 0.69 with solvent excluded).…”
Section: Resultsmentioning
confidence: 99%
“…The design of coordination polymers with a predictable secondary building unit (SBU) and dimensionality is a quasi-impossible task but the quest remains of great interest for the discovery of new materials with desired properties such as gas adsorption, [1][2][3][4][5][6][7][8][9] sensing, [10][11][12][13][14][15] thermochromism, [16][17][18][19] magnetism, [20][21][22][23][24] conductivity, [25][26][27][28] redox-activity, 29,30 catalysis, 13,[31][32][33] nonlinear optical behavior 34,35 and luminescence. 8,[36][37][38][39][40] Recent reviews on CPs formed by mono-and dithioethers with CuX salts (X = Cl, Br, I) [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…The design of coordination polymers with a predictable secondary building unit (SBU) and dimensionality is a quasi-impossible task, but the quest remains of great interest for the discovery of new materials with desired properties such as gas adsorption, sensing, thermo-chromism, magnetism, conductivity, redox-activity, , catalysis, , nonlinear optical behavior, , and luminescence. , Recent reviews on CPs formed by mono- and dithioethers with CuX salts (X = Cl, Br, I) revealed that, when X = I, the SBU had a strong tendency to form closed cubanes (Cu 4 I 4 ) and 1D staircase polymeric structures, whereas the rhomboid Cu 2 X 2 S 4 SBU is predominately noted when X = Cl or Br. The key property is that the cubanes show luminescence regardless of the ligand, whereas the rhomboids and staircase motifs are almost always weakly or not emissive. ,, Also, the presence of 2D and 3D CPs increases drastically when semirigid or rigid dithioethers are used as assembling ligands. ,, The interest in 2D and 3D CPs stems from the possibility to form MOF-like materials .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all of the 4-coordinated Ln­(III) centers are in a row and all of the Cu­(I) centers occupy alternate rows in the pentagon tiling. Such Cairo tiling structures (Figure b) has also been observed in other 2D MOFs. …”
Section: Design Strategiesmentioning
confidence: 99%